Safety and immunogenicity of an HIV-1 gp120-CD4 chimeric subunit vaccine in a phase 1a randomized controlled trial. Issue 29 (29th June 2021) - Chua, Joel V.; Davis, Charles; Husson, Jennifer S.; Nelson, Amy; Prado, Ilia; Flinko, Robin; Lam, Ka Wing J.; Mutumbi, Lydiah; Mayer, Bryan T.; Dong, Dan; Fulp, William; Mahoney, Celia; et al.
Abstract: A major challenge for HIV vaccine development is to raise anti-envelope antibodies capable of recognizing and neutralizing diverse strains of HIV-1. Accordingly, a full length single chain (FLSC) of gp120-CD4 chimeric vaccine construct was designed to present a highly conserved CD4-induced (CD4i) HIV-1 envelope structure that elicits cross-reactive anti-envelope humoral responses and protective immunity in animal models of HIV infection. IHV01 is the FLSC formulated in aluminum phosphate adjuvant. We enrolled 65 healthy adult volunteers in this first-in-human phase 1a randomized, double-blind, placebo-controlled study with three dose-escalating cohorts (75 µg, 150 µg, and 300 µg doses). Intramuscular injections were given on weeks 0, 4, 8, and 24. Participants were followed for an additional 24 weeks after the last immunization. The overall incidence of adverse events (AEs) was not significantly different between vaccinees and controls. The majority (89%) of vaccine-related AE were mild. The most common vaccine-related adverse event was injection site pain. There were no vaccine-related serious AE, discontinuation due to AE, intercurrent HIV infection, or significant decreases in CD4 count. By the final vaccination, all vaccine recipients developed antibodies against IHV01 and demonstrated anti-CD4i epitope antibodies. The elicited antibodies reacted with CD4 non-liganded Env antigens from diverse HIV-1 strains. Antibody-dependent cell-mediated cytotoxicity against heterologous infected cells or gp120 bound to CD4+ cells was evident in all cohorts as were anti-gp120 T -cell responses. IHV01 vaccine was safe, well tolerated, and immunogenic at all doses tested. The vaccine raised broadly reactive humoral responses against conserved CD4i epitopes on gp120 that mediates antiviral functions.